Diagnostik holistik tuberkulosis paru anak di Puskesmas Bailang - Henry M. F. Palandeng; Michelle Wilhelmina Mandang (UNIVERSITAS SAM RATULANGI, 2022)
Tuberculosis is a disease that is transmitted through the air by the bacterium Mycobacterium tuberculosis (M. tuberculosis). Tuberculosis usually attacks the lungs, but can also attack the extrapulmonary (larynx, lymph nodes, pleura, kidneys, bones and joints). Patients with pulmonary tuberculosis usually have symptoms such as coughing, sweating, especially at night, fever, fatigue, and weight loss. In 2015, pediatric TB cases accounted for 9% of all TB cases in Indonesia.In this case discussion there is a patient diagnosed with pulmonary tuberculosis. The patient came with a complaint of cough with phlegm for approximately 1 month. The patient has done a sputum test / culture, and the results are positive, the patient has finished undergoing initial phase of OAT treatment therapy, and is undergoing an advanced phase of therapy. This discussion is about a holistic diagnostic approach to the patient's disease. This is done in order to know better about the factors related to the occurrence of the disease in patients.Â